A copper‐induced quinone degradation pathway provides protection against combined copper/quinone stress in Lactococcus lactis IL1403. Issue 4 (30th December 2014) - Mancini, Stefano; Abicht, Helge K.; Gonskikh, Yulia; Solioz, Marc
Summary Quinones are ubiquitous in the environment. They occur naturally but are also in widespread use in human and industrial activities. Quinones alone are relatively benign to bacteria, but in combination with copper, they become toxic by a mechanism that leads to intracellular thiol depletion. Here, it was shown that the yahCD‐yaiAB operon of Lactococcus lactis IL1403 provides resistance to combined copper/quinone stress. The operon is under the control of CopR, which also regulates expression of the copRZA copper resistance operon as well as other L. lactis genes. Expression of the yahCD‐yaiAB operon is induced by copper but not by quinones. Two of the proteins encoded by the operon appear to play key roles in alleviating quinone/copper stress: YaiB is a flavoprotein that converts p‐benzoquinones to less toxic hydroquinones, using reduced nicotinamide adenine dinucleotide phosphate (NADPH) as reductant; YaiA is a hydroquinone dioxygenase that converts hydroquinone putatively to 4‐hydroxymuconic semialdehyde in an oxygen‐consuming reaction. Hydroquinone and methylhydroquinone are both substrates of YaiA. Deletion of yaiB causes increased sensitivity of L. lactis to quinones and complete growth arrest under combined quinone and copper stress. Copper induction of the yahCD‐yaiAB operon offers protection to copper/quinone toxicity and could provide a growth advantage to L. lactis in some environments.